Małoocze z olbrzymią torbielą oczodołu – opis przypadku - Urban, Beata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
Authors present rare case of microphthalmos with large cyst in 8-years old healthy girl. She was referred because of progressive exophthalmos of hypoplastic left eyeball and slight ptosis and bulge of upper lid. Magnetic resonance demonstrated the large lesion filling whole left orbit. There was no communication to the intracranial space. This lesion was excised. It was giant orbital cyst filled with fluid and was growing together with deformed globe.